FINANCIAL STATEMENT INTEGRITY: THE ROLE OF AUDIT TENURE, KAP SIZE, AND AUDIT FEE - Vivian Susanto; Khairudin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to determine and analyze the impact of audit tenure, the size of KAP, and audit fees. The purpose of this study is to disseminate knowledge and information about factors that affect the integrity of financial statements of building construction companies in Indonesia. The object of this study is a building construction sub-sector company listed on the Indonesia Stock Exchange during the period 2020 – 2022. The entire quantitative research sample amounted to 33 companies. Purposive sampling is used in the sampling procedure. The test was conducted using multiple regression analysis, where the integrity of financial statements is measured using accounting conservatism. The results of this study show that tenure audits and audit fees have a negative and significant effect on the integrity of financial statements and the size of public accounting has a positive and significant effect on the integrity of financial statements. It is expected that with this research, all parties (management, shareholders, and auditors) must be highly committed to realizing the improvement of financial statement integrity. The limitation of this study is the low adjusted R square value of 0.271, which indicates that the independent variable is only able to explain 27.1% of the variation of the dependent variable, as well as the lack of research samples. Then the suggestion for future research is to add research samples and other variables such as (1) company size; (2) leverage; (3) profitability; (4) financial distress that can explain the effect on the integrity of financial statements.